Hubungan Pengembangan Karir dengan Kinerja Guru di SMA Negeri 1 Kandis Kecamatan Kandis Kabupaten Ogan Ilir - Febriyanti Febriyanti (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2017)
Human Resource Development is an activity to maintain and improve employee competence in order to achieve organizational effectiveness. Human Resource Development can be realized through career development, as well as education and training This research is to know the Relationship of Career Development with Teacher Performance in Public High School 1 Kandis, Kandis Sub-district, Ogan Ilir District. Research methodology with the type of research used is (field research) direct research conducted with quantitative approach. Types of data are quantitative and qualitative with primary data sources and secondary data sources of literature on the subject matter. The population in this study is all teachers in Public High School 1 Kandis, Kandis Sub-district, Ogan Ilir District, amounting to 28 people. Technique of collecting data using Observation, Questionnaire (Questionnaire) and Technique. To analyze the data will be used statistical formula, namely the formula of Correlation Coefficient of Contigency Engineering. Teacher career development in the moderate category where 21 people with percentage of 75%, 4 people with percentage of 14.29%, and 4 people with 10.71% percentage. While the performance of teachers including medium category, where 19 respondents with percentage of 67.86%, 5 respondents with the percentage of 17.86%, and for 4 respondents with the percentage of 14.29%. Based on cotigence correlation analysis, there was a significant positive correlation between career development with proven teacher performance of Phi greater than rtabel, good at 5% level.